2014
DOI: 10.1016/j.sbspro.2014.11.238
|View full text |Cite
|
Sign up to set email alerts
|

Tax Burden Level Leverage on Size of the Shadow Economy, Cases of EU Countries 2003-2013

Abstract: The burden of taxation and social security levels are combined with rising activities of the state regulatory. Fiscal and social policies in the current economic times are becoming one of the most important formal driving forces controlling the shadow economy levels in EU. Spearman's correlational coefficients connections between changes of the social contributions, along with its benefits, tax burden structure elements (% of GDP ratio) are used to discern impact for the shadow economy's level and the aim is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…According to Feld and Schneider's summary of 32 studies on the shadow economy and its causes, "increase of the tax and social security contribution burdens" was by far the most important single contributor to the increase of the shadow economy, followed by "tax morale," "quality of state institutions," and "specific labor market regulations" (2010). However, contrary to traditional thinking that the tax burden is a significant driver of the shadow economy, some scholars have presented opposing empirical research results showing that the tax burden has a negative correlation with the shadow economy (Friedman, Johnson, and Kaufmann 2000;Stankevičius and Vasiliauskaite 2014). Cumbersome labor-market restrictions, loss of access to the formal financial sector, and weak governance and institutions also determine the size of the shadow economy (Singh, Jain-Chandra, and Mohommad 2012).…”
Section: What Are the Key Characteristics Of The Shadow Economy?mentioning
confidence: 98%
“…According to Feld and Schneider's summary of 32 studies on the shadow economy and its causes, "increase of the tax and social security contribution burdens" was by far the most important single contributor to the increase of the shadow economy, followed by "tax morale," "quality of state institutions," and "specific labor market regulations" (2010). However, contrary to traditional thinking that the tax burden is a significant driver of the shadow economy, some scholars have presented opposing empirical research results showing that the tax burden has a negative correlation with the shadow economy (Friedman, Johnson, and Kaufmann 2000;Stankevičius and Vasiliauskaite 2014). Cumbersome labor-market restrictions, loss of access to the formal financial sector, and weak governance and institutions also determine the size of the shadow economy (Singh, Jain-Chandra, and Mohommad 2012).…”
Section: What Are the Key Characteristics Of The Shadow Economy?mentioning
confidence: 98%
“…All the authors cited agree with the idea that high income taxation has a negative impact on economic growth and countries development. Budgetary discipline and good allocation of resources by governments of the different member states are also essential to the economic and social success [23].…”
Section: The "Fiscal Gap" Between Eu Member States and How It Affectsmentioning
confidence: 99%
“…Other main determinants concern with the taxation regime and institutional setting. The studies by [19], [20] and [21] found that the burden of taxation is among the main determinants in the EU countries and particularly in Spain ( [22]). [23] pointed out that bureaucratic complexity also contributes to the SE.…”
Section: On the Determinants Of The Shadow Economymentioning
confidence: 99%